NUMERICAL EVALUATION OF SEISMIC PERFORMANCE OF CORRUGATED-PLATE SHAPED STEEL TUBES - Al-Kaseasbeh, Qusay; Albarram, Ahmed (Journal of Applied Engineering Science, 2022)
The current work presents a unique study on the seismic performance of innovative corrugated-plate steel bridge piers. While several previous research was conducted on steel tubes with cross sections such as rounded or semi triangular plates, the seismic performance of such structural members with straight ribbed corrugation geometry under uniaxial cyclic loading remained a research gap. Thus, this research aims to present a new concept that could add a promising design to steel tubes under seismic effect. The seismic performance of such piers was numerically investigated in terms of the load-bearing capacity and local buckling. ABAQUS was employed to accomplish a series of finite element analyses on corrugated-plate steel bridge piers under constant axial dead load and lateral cyclic displacement. Three different geometries of corrugated-shaped steel tubes (i.e., C60, C80, and C146 mm deep) along with four different thicknesses (i.e., 6, 8, 10, and 12 mm) were investigated and compared to the traditional circular-shaped steel tubes (i.e., Cir) having same thicknesses and outer diameter. The results revealed that the innovative corrugated-plate steel bridge piers offered 20% greater load-bearing capacity and 66% more ductility compared to their companions of circular-shaped steel tubes. It was interesting to notice that the peak value of the load-bearing capacity of the C146 column was greater than those of the C80 and C60 columns by 7% and 10%, respectively. Furthermore, the local buckling was generally seen less severe amongst corrugated-plate steel bridge piers. This research raises the importance of corrugated-plate sections used in bridge piers over circular shapes owing to their advantages in strength and aestheticism.